Embodied, Affective and Connected Science Education for A Sustainable World - Blom, Simone M. (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Sustainability and environmental education are often taught through the Science discipline in the curriculum. The biological sciences accommodate much of the work students will do in learning about ecological, biological and sustainable practices and systems of the living world. This work is important, however, it can focus too heavily on content without paying attention to the natural environment to enable students to experience embodied and affective responses. Learning about the human body with/as nature is and should be an essential aspect of science education. Learning about the human body is typically achieved through the biological sciences curriculum and is not considered in relationship to the natural world and the environmental crisis. In science education we have the opportunity to consider our embodied relationship with/as the natural world and how this fundamental relationship may shift thinking of the environmental crisis as happening ‘out there’. This opportunity transforms our thinking from trying to fix the problem using exterior solutions to considering our responsibility as intrinsically connected human bodies. This research presentation explores the affective turn to consider how our embodied relationship with nature can be activated as an educational apparatus to enhance sustainable practices. Sustainable solutions cannot be considered devoid of the human body that is made of the same biological matter that forms the natural world. This presentation proposes an education that is embodied, affective and connected for a sustainable future world.